2005
DOI: 10.1063/1.1940053
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of fluids near the consolute critical point: A molecular-dynamics study of the Widom–Rowlinson mixture

Abstract: Molecular-dynamics simulations are presented for the dynamic behavior of the Widom-Rowlinson mixture [B. Widom, and J. S. Rowlinson, J. Chem. Phys. 52, 1670 (1970)] at its critical point. This model consists of two components where like species do not interact and unlike species interact via a hard-core potential. Critical exponents are obtained from a finite-size scaling analysis. The self-diffusion coefficient shows no anomalous behavior near the critical point. The shear viscosity and thermal conductivity s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 89 publications
1
7
0
Order By: Relevance
“…4, but in the high-frequency interval: = 10 (1 ), 25 (2 ), 30 (3 ), 50 (4 ), 110 (5 ), and 300 MHz (6 ) in Fig. 3, c, as well as similar plots for other examined binary solutions [12,13], testify that the fluctuation part of the sound absorption coefficient is smaller than the regular part even along the critical isotherm and isoconcentrate. Therefore, our research cancels the inequality…”
Section: Three-dimensional Representations For the Sound Absorption Csupporting
confidence: 61%
See 1 more Smart Citation
“…4, but in the high-frequency interval: = 10 (1 ), 25 (2 ), 30 (3 ), 50 (4 ), 110 (5 ), and 300 MHz (6 ) in Fig. 3, c, as well as similar plots for other examined binary solutions [12,13], testify that the fluctuation part of the sound absorption coefficient is smaller than the regular part even along the critical isotherm and isoconcentrate. Therefore, our research cancels the inequality…”
Section: Three-dimensional Representations For the Sound Absorption Csupporting
confidence: 61%
“…Hence, the analysis of the experimental and literature data obtained for the sound absorption coefficient in binary or ternary solutions [12,13] showed that the considered abnormal non-universal temperature dependences are observed, if the temperature dependences of the sound absorption coefficient are different -decreasing or increasing -for the pure components of the examined solutions. This conclusion is definitely confirmed by the experimental data obtained for the temperature dependences of the sound absorption coefficient in the frequency interval ≫ ≫ 110 MHz.…”
Section: Peculiarities In the Behavior Of The Sound Absorption Coeffimentioning
confidence: 99%
“…On the other hand, the situation with respect to dynamics is relatively poor. Simulation studies, that helped achieving the objective for the static phenomena, gained momentum in the context of dynamic critical phenomena only recently [25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Such a status is despite the fact that adequate information on the equilibrium transport phenomena is very much essential for the understanding of even nonequilibrium phenomena like the kinetics of phase transitions [9,39].…”
Section: Introductionmentioning
confidence: 99%
“…1,3,4 Due to this reason, simulation studies of the dynamic critical phenomena are very recent. [5][6][7][8][9][10][11] In the vicinity of a critical point, various static and dynamic properties exhibit power-law singularities. 1,[12][13][14] For example, in static critical phenomena, the correlation length (ξ ), the order parameter (m), and the susceptibility (χ ) behave as 1,12 …”
Section: Introductionmentioning
confidence: 99%
“…In computer simulations, reliable calculations of collective transport properties [1,3], e.g., shear (η) and bulk (ζ) viscosities, thermal diffusivity (D T ), mutual diffusivity (D AB ) in a (A + B) binary mixture, etc., are extremely difficult due to lack of self averaging [1,3,4]. Simulation studies of dynamic critical phenomena, because of this reason, have started only recently [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%